2023
DOI: 10.58526/jsret.v2i2.145
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Triage in Service in The Emergency Department (Literature Review)

Abstract: Service accuracy is the minimum standard of service that must be achieved by nurses in the emergency room, so that proper triage implementation is needed. Triage is the classification of patients based on the level of emergency by prioritising actions on airway (A), breathing (B), and circulation (C) disorders by considering facilities, human resources and the probability of patient life. The literature search in this literature review uses six databases with high and medium quality criteria, namely scient dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Several previous studies, such as those conducted by (Saban et al, 2019;Soemah, 2023), have shown a relationship between nurse response time and the accuracy of triage assessments. The results of this study confirmed that nurse response time has a significant correlation with the accuracy of triage assessment at the emergency room of Sele Be Solu Hospital, Sorong City.…”
Section: Discussionmentioning
confidence: 92%
“…Several previous studies, such as those conducted by (Saban et al, 2019;Soemah, 2023), have shown a relationship between nurse response time and the accuracy of triage assessments. The results of this study confirmed that nurse response time has a significant correlation with the accuracy of triage assessment at the emergency room of Sele Be Solu Hospital, Sorong City.…”
Section: Discussionmentioning
confidence: 92%